FeNO in Asthma - Loewenthal, Lola; Menzies-Gow, Andrew (Seminars in Respiratory and Critical Care Medicine, 2022)
Asthma is a common disease affecting 350 million people worldwide, which is characterized by airways inflammation and hyperreactivity. Historically diagnosis and treatment have been mainly based on symptoms, which have the potential to result in misdiagnosis and inappropriate treatment. Nitric oxide (NO) is exhaled in human breath and is a marker of airways inflammation. Levels of NO are increased in the exhaled breath of patients with type 2 asthma and fractional exhaled nitric oxide (FeNO) provides an objective biomarker of airway inflammation. FeNO testing is an accessible, noninvasive, and easy-to-use test. Cut-off values have been established by the American Thoracic Society (ATS), the Global Initiative for Asthma (GINA), and the National Institute for Health and Care Excellence (NICE) but vary between guidance. FeNO levels have been shown to be predictive of blood and sputum eosinophil levels but should not be used in isolation and current guidance emphasizes the importance of incorporating clinical symptoms and testing when utilizing FeNO results. The inclusion of FeNO testing can increase diagnostic accuracy of asthma, while high levels in asthmatic patients can help predict response to inhaled corticosteroids (ICS) and suppression of levels with ICS to monitor adherence. FeNO levels are also a predictor of asthma risk with increased exacerbation rates and accelerated decline in lung function associated with high levels as well as having an emerging role in predicting response to some biologic therapies in severe asthma. FeNO testing is cost-effective and has been shown, when combined with clinical assessment, to improve asthma management.
Keywords: asthma; biomarkers; diagnosis; fraction of exhaled nitric oxide; management; monitoring; type 2 inflammation